2010
DOI: 10.1111/j.1750-2659.2010.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

The relative efficacy of trivalent live attenuated and inactivated influenza vaccines in children and adults

Abstract: In the United States, two types of vaccines are recommended for the prevention of influenza: an intranasal live attenuated influenza vaccine (LAIV) for eligible individuals aged 2–49 years and unadjuvanted injectable trivalent inactivated vaccines (TIV) for eligible individuals aged ≥6 months. Several recent studies have compared the efficacy of the 2 vaccines in children and adults. In children 6 months to 18 years of age, each of the four comparative studies of LAIV and TIV demonstrated that LAIV was more pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
116
0
14

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(135 citation statements)
references
References 32 publications
1
116
0
14
Order By: Relevance
“…A 2011 review of studies comparing TIV and LAIV concluded that the two vaccines have a similar relative efficacy in the elderly, based on the currently available data. [225] In South Africa, a randomized placebo-controlled trial in 2001 estimated LAIV efficacy against vaccine-matched influenza viruses to be 42.3%, with highest efficacy against influenza A(H3N2) viruses (52.5%), no efficacy against influenza B viruses, and no increase of severe adverse events for LAIV recipients compared to placebo. [226] A superiority trial in South Africa in 2002 found no significant difference in relative efficacy between LAIV and TIV, although this was due in part to the small number of laboratory-confirmed infections in the two study arms.…”
Section: Vaccine Performancementioning
confidence: 99%
“…A 2011 review of studies comparing TIV and LAIV concluded that the two vaccines have a similar relative efficacy in the elderly, based on the currently available data. [225] In South Africa, a randomized placebo-controlled trial in 2001 estimated LAIV efficacy against vaccine-matched influenza viruses to be 42.3%, with highest efficacy against influenza A(H3N2) viruses (52.5%), no efficacy against influenza B viruses, and no increase of severe adverse events for LAIV recipients compared to placebo. [226] A superiority trial in South Africa in 2002 found no significant difference in relative efficacy between LAIV and TIV, although this was due in part to the small number of laboratory-confirmed infections in the two study arms.…”
Section: Vaccine Performancementioning
confidence: 99%
“…Furthermore, we identified one observational study in children aged 5-18 years [8], which we excluded from further analysis because study participants in the intervention group differed substantially in baseline risk for influenza from those in the comparison group (healthy children were vaccinated with LAIV, children with increased risk of influenza due to an underlying chronic condition were vaccinated with TIV). In addition, we found five publications with meta-analyses and/or subgroup analyses of efficacy and safety data from these three studies and placebo-controlled studies of LAIV [4,9,10,11,12], which we additionally considered in the evidence appraisal process.…”
Section: Methodsmentioning
confidence: 99%
“…Absolute efficacy in 18-49 year olds was lower than in children and efficacy was not demonstrated in the over 50s, leading to preferential recommendation for LAIV in children. 6,42 The common interpretation of this finding is that adults have prior immune history of influenza infections and possess cellular immunity to conserved internal viral proteins that can supress local mucosal replication of LAIV well enough to preclude a robust immune response. This cross-reactive immunity may be what protects many adults from severe illness during a pandemic.…”
Section: (Ii)prior Vaccination and Immunitymentioning
confidence: 99%
“…4,5 More recently, live attenuated influenza vaccine (LAIV) was demonstrated to have greater efficacy than IIV in children, with absolute efficacy rates of 75-80%. [6][7][8] Internal genes of LAIV viruses are derived from a cold-adapted, attenuated strain of virus, either Ann Arbor/1960 (from the US) or Leningrad/1957 (from Russia). Haemagglutinin (HA) and neuraminidase (NA) surface antigens are engineered to be representative of currently circulating strains.…”
mentioning
confidence: 99%